Digital Sensemaking and Shared Leadership among Women Posyandu Cadres - Meranti Hasbiran; Alifiana Khairunnisa; Annisa Utami Seminar; Amiruddin Saleh; Mimi Fitriana (MEDIASI Jurnal Kajian dan Terapan Media, Bahasa, Komunikasi, 2026)
Community-based health volunteer organizations have emerged as critical yet undertheorized sites of organizational communication, particularly in the Global South. This study examines how digital sensemaking processes contribute to the emergence of shared leadership among women Posyandu cadres in Pejaten Barat, South Jakarta, Indonesia. Adopting a qualitative case study design, data were collected through in-depth interviews, non-participant observation, and document analysis involving six cadres at Posyandu Nangka II. Guided by Weick's Organizational Information Theory and the shared leadership framework, the study analyzes how cadres interpret, negotiate, and retain organizational information through both face-to-face interaction and WhatsApp-mediated communication. The findings demonstrate that WhatsApp functions not merely as a message channel but as a digital sensemaking arena, enabling cadres to reduce equivocality, coordinate activities, and construct shared understandings of tasks and responsibilities. These processes facilitate the distribution of leadership functions beyond formal hierarchical structures, allowing active members to assume coordination and decision-making roles when formal leadership is absent or passive. The study argues that shared leadership in this context emerges through continuous communicative practices rather than formal authority. The novelty of this study lies in extending Weick's sensemaking framework into digitally mediated, women-led volunteer settings a context that has received limited attention in organizational communication research. Findings offer practical insights for strengthening women's participation, coordination, and leadership capacity in community-based health programs through digital communication platforms.